Palladium-Catalyzed Synthesis of Indene Derivatives via Intramolecular Allylic Arylation of Baylis–Hillman Acetates - Shao, Jiangbin; Hu, Peizhu; Hong, Guo; Fang, Mingwu; Li, Xiaoqing; Xu, Xiangsheng (Synlett, 2014)
An intramolecular allylic arylation protocol for the synthesis of indene derivatives from readily available Baylis–Hillman acetates via palladium-catalyzed C–H bond activation has been developed.
Keywords: palladium; C–H bond activation; indene derivatives; Baylis–Hillman acetates; intramolecular allylic arylation